Recent Advances in Design and Signal Processing for Antenna Arrays 2020 - Liu, Wei; Madanayake, Arjuna; Yu, Lei; Shen, Qing; Cai, Jingjing (International journal of antennas and propagation, 2023)
Compared with a single physical antenna, an antenna array has the capability for effective interference suppression/beamforming, direction of arrival (DOA) estimation, target tracking, and localization with its additional spatial degrees of freedom (DOFs) exploited by advanced signal processing algorithms [1–4]. In particular, the antenna array design and signal processing is one of the fundamental techniques in wireless communication systems of the 5G and beyond since the two underpinning 5G technologies, massive multiple-input multiple-output (MIMO) and millimetre wave communications, are all based on antenna array systems [6, 7]. The first topic is antenna design for array applications, including one paper titled “Development of a Pin Diode-Based Beam-Switching Single-Layer Reflectarray Antenna” [12]; the second topic is antenna array pattern synthesis, including one paper titled “Two-Dimensional Beampattern Synthesis for Polarized Smart Antenna Array and Its Sparse Array Optimization” [13]; the third topic is direction/angle of arrival estimation, including two papers, titled “Thinned Virtual Array for Cramer Rao Bound Optimization in MIMO Radar” and “Nonuniformly Spaced Array with the Direct Data Domain Method for 2D Angle-of-Arrival Measurement in Electronic Support Measures Application from 6 to 18 GHz” [14, 15], respectively; the last topic is target detection and localization (range/velocity/angle estimation) based on antenna arrays, including two papers, titled “Spread Sea Clutter Suppression in HF Hybrid Sky-Surface Wave Radars Based on General Parameterized Time-Frequency Analysis” and “Maximum Likelihood Angle-Range Estimation for Monostatic FDA-MIMO Radar with Extended Range Ambiguity Using Subarrays” [16, 17], respectively.